Computational study of the effects of arterial bifurcation on the temperature distribution during cryosurgery - Zheng, Yong-Chang; Wu, Jun-Hong; He, Zhi-Zhu; Huang, Shao-Jiong (Biomedical engineering online, 2018)
Thermally significant blood flows into locally cooled diseased tissues and warm them during cryosurgery so that the iceball is often hard to cover the whole diseased volume. This paper is aimed at investigating the effects of large arterial bifurcation on the temperature distribution during cryosurgery through simulation method. A parametric geometry model is introduced to construct a close-to-real arterial bifurcation. The three-dimensional transient conjugate heat transfer between bifurcated artery and solid tissues with phase change during cryosurgery is performed by finite volume method. The discussion was then made on the effects of the relative position between cryoprobe and artery bifurcation, the inlet velocity of root artery and the layout of multiple cryoprobes on the temperature distribution and iceball evolution. The results show that the thermal interaction between blood flow and iceball growth near bifurcation is considerable complex. The thermal effects of bifurcation could modulate the iceball morphology, severely weaken its freezing volume and prevent the blood vessel from being frozen. The present work is expected to be valuable in optimizing cryosurgery scheme of the situation that the bifurcated artery is embedded into the disease tissue.